#OceanOptimism: Balancing the Narrative About the Future of the Ocean - Borja, Angel; Elliott, Michael; Basurko, Oihane C.; Fernández Muerza, Alex; Micheli, Fiorenza; Zimmermann, Fabian; Knowlton, Nancy (Frontiers in Marine Science, 2022)
The ocean is facing multiple pressures from human activities, including the effects of climate change. Science has a prominent role in identifying problems and communicating these to society. However, scientists are also increasingly taking an active role in developing solutions, including strategies for adapting to and mitigating climate change, increasing food security, and reducing pollution. Transmitting these solutions to society changes our narrative about the ocean and motivates actions. The United Nations triple initiatives for this decade - the Sustainable Development Goals, the Decade on Ocean Science for Sustainable Development and the Decade of Ecosystem Restoration – provide the momentum for this change in narrative and focus. Here we reflect on the search for solutions and the need for better ways of communicating science in a positive way. We synthesize insights from a Summer School held during the COVID-19 pandemic and present some examples of successes and failures and the lessons learned from these.